2009
DOI: 10.1111/j.1600-0633.2008.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation reveals fine‐scale genetic structure of masu salmon, Oncorhynchus masou, within the Atsuta River

Abstract: To describe in detail the population genetic structure of masu salmon Oncorhynchus masou, seven anadromous populations in the Atsuta River were investigated by analysis of eight polymorphic microsatellite loci. Exact test and genetic differentiation (F ST ) revealed that significant differentiation was observed at the within-river scale. Principal components analysis revealed that the spatial pattern of genetic composition was related to geographical location of each population. Furthermore, a significant corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…In the below-dam region, although the levels of genetic differentiation estimated by F ST were week, significant genetic differentiation and IBD were observed, implying that gene flow may be more likely to occur between neighboring populations (Primmer et al 2006). These results are concordant with previous studies, which demonstrated that masu salmon have the potential to show genetic structuring at the local scale due to their homing behavior (the Atsuta River, sea of Japan side of Hokkaido; Kitanishi et al 2009). In contrast to the below-dam region, no evidence of IBD was revealed above the dam, despite the significant genetic differentiation within this area.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In the below-dam region, although the levels of genetic differentiation estimated by F ST were week, significant genetic differentiation and IBD were observed, implying that gene flow may be more likely to occur between neighboring populations (Primmer et al 2006). These results are concordant with previous studies, which demonstrated that masu salmon have the potential to show genetic structuring at the local scale due to their homing behavior (the Atsuta River, sea of Japan side of Hokkaido; Kitanishi et al 2009). In contrast to the below-dam region, no evidence of IBD was revealed above the dam, despite the significant genetic differentiation within this area.…”
Section: Discussionsupporting
confidence: 95%
“…No case of LD was detected systematically for the same pair of loci across different populations. In addition, some loci showed no evidence of LD in a previous study (Kitanishi et al 2009). Therefore, we used the entire suite of 10 microsatellite loci and treated them as being independent.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Quinn et al (2006) present evidence of very fine scale homing in sockeye salmon. Genetic evidence has shown that masu salmon (Oncorhynchus masou) have clear genetic structure at the microgeographical scale (21 km) due to precise homing behaviour (Kitanishi et al, 2009). …”
Section: Habitat Selection or Homing?mentioning
confidence: 99%